A lexical semantic approach to interpreting and bracketing English noun compounds. (30th May 2013) - KIM, SU NAM; BALDWIN, TIMOTHY
Abstract: This paper presents a study on the interpretation and bracketing of noun compounds ('NCs') based on lexical semantics. Our primary goal is to develop a method to automatically interpret NCs through the use of semantic relations. Our NC interpretation method is based on lexical similarity with tagged NCs, based on lexical similarity measures derived from WordNet. We apply the interpretation method to both two- and three-term NC interpretation based on semantic roles. Finally, we demonstrate that our NC interpretation method can boost the coverage and accuracy of NC bracketing.